Transcultural Practices of International Students as Identity Performances in Digital Settings - Solmaz, Osman (Journal of Interdisciplinary Studies in Education, 2021)
Guided by an interdisciplinary approach, this study seeks to illustrate the digital practices of international speakers on social media. The practices of international users are especially valuable due to the presence of various audiences in their networks, some rarely researched. For this purpose, the study examines the social media practices of 16 international graduate students (IGSs), who experience a transnational mobility in the United States. The data is collected through semi-structured interviews with participants and their social media data. The analysis includes quantitative assessment of participants’ social media activities and qualitative analyses of interviews and digital practices. The findings of the study illustrate how individuals with transborder experiences engage in identity work by sharing transcultural content with a multitude of audiences in their networks. The study concludes that digital practices involving the transcultural flow of content present opportunities for IGSs to work and realign various facets of their identities.